doublesex Controls Both Hindwing and Abdominal Mimicry Traits in the Female-Limited Batesian Mimicry of Papilio memnon - Komata, Shinya; Lin, Chung-Ping; Fujiwara, Haruhiko (Frontiers in Insect Science, 2022)
Papilio butterflies are known to possess female-limited Batesian mimicry polymorphisms. In Papilio memnon, females have mimetic and non-mimetic forms, whereas males are monomorphic and non-mimetic. Mimetic females are characterized by color patterns and tails in the hindwing and yellow abdomens. Recently, an analysis of whole-genome sequences has shown that an approximately 160 kb region of chromosome 25 is responsible for mimicry and has high diversity between mimetic (A) and non-mimetic (a) alleles (highly diversified region: HDR). The HDR includes three genes, UXT, doublesex (dsx), and Nach-like, but the functions of these genes are unknown. Here, we investigated the function of dsx, a gene involved in sexual differentiation, which is expected to be functionally important for hindwing and abdominal mimetic traits in P. memnon. Expression analysis by reverse transcription quantitative PCR (RT-qPCR) and RNA sequencing showed that mimetic dsx (dsx-A) was highly expressed in the hindwings in the early pupal stage. In the abdomen, both dsx-A and dsx-a were highly expressed during the early pupal stage. When dsx was knocked down using small interfering RNAs (siRNAs) designed in the common region of dsx-A and dsx-a, a male-like pattern appeared on the hindwings of mimetic and non-mimetic females. Similarly, when dsx was knocked down in the abdomen, the yellow scales characteristic of mimetic females changed to black. Furthermore, when dsx-a was specifically knocked down, the color pattern of the hindwings changed, as in the case of dsx knockdown in non-mimetic females but not mimetic females. These results suggest that dsx-a is involved in color pattern formation on the hindwings of non-mimetic females, whereas dsx-A is involved in hindwing and abdominal mimetic traits. dsx was involved in abdominal and hindwing mimetic traits, but dsx expression patterns in the hindwing and abdomen were different, suggesting that different regulatory mechanisms may exist. Our study is the first to show that the same gene (dsx) regulates both the hindwing and abdominal mimetic traits. This is the first functional analysis of abdominal mimicry in butterflies.